PROJECTION ANALYSIS OF CHANGES IN FIXED ASSETS grouping LISTED ON COMPUTER ACCOUNTING Ministerial decree BASED No.KMK138/KMK.03/2002. - HERU HERU SUHARJO (Majalah SIKOMTEK, 2005)
The policy changes in the grouping of Fixed Assets will be an obstacle for Accountants and taxpayers to analyze the projections pencataatn, particularly the application of Computer Equipment pencataan calculations. While the goals to be reach of this paper is: To determine changes in the grouping of Fixed Assets by application of recording fixed assets, especially Computer calculations are based on the Decree of the Minister of Finance KMK 138/KMK..03/2002. The method used to compare the analysis with the method of calculating the projection of a straight line and declining balance method. As a result of this discussion, because the value of obsolete and value the benefits of Fixed Assets Computers so quick to encourage policy changes in the grouping of Fixed Assets, the Fixed Assets Computer need penyesuaikan groupings.